Super-hydrophobic matte composite coating and preparation method thereof

By electroplating semi-gloss nickel layer, pearl nickel layer and trivalent chromium layer on kitchen and bathroom products, and forming a silica layer under vacuum, a highly translucent and wear-resistant superhydrophobic matte composite coating was constructed, and the solution was solved The impact of surface stains on kitchen and bathroom products and the degradation of hydrophobic performance has achieved efficient superhydrophobic performance maintenance.

CN119194550APending Publication Date: 2024-12-27WATER BOGER HARDWARE SHENZHEN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411121748.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The superhydrophobic surfaces of kitchen and bathroom products are easily affected by stains during use, and the powder spraying method causes the transparency and color surfaces to be inapplicable, and the hydrophobic performance is greatly reduced after wear, making it difficult to maintain superhydrophobic performance.

Method used

By electroplating semi-optic nickel layer, pearl nickel layer and trivalent chromium layer on the ABS substrate, and forming a 10-20nm thick silicon dioxide layer under vacuum conditions, a superhydrophobic matte composite coating is constructed with low surface energy and Wear resistance.

Benefits of technology

Achieves a superhydrophobic surface with high light transmission and diffuse reflection, maintaining contact angle greater than 153° and rolling angle less than 10°, and still has superhydrophobic properties after wear, with dense and wear-resistant surfaces, and a matte effect of pearl satin color .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194550A_ABST
    Figure CN119194550A_ABST
Patent Text Reader

Abstract

The super-hydrophobic matte composite coating provided by the invention comprises an ABS (Acrylonitrile Butadiene Styrene) base material; a semi-bright nickel layer, a pearl nickel layer and a trivalent chromium layer are sequentially electroplated on the upper surface of the bottom layer of the ABS base material to form a hydrophobic structure layer; under the vacuum condition, ion plating is carried out on the surface of the hydrophobic structure layer of the ABS base material to form a silicon dioxide layer with the thickness of 10-20 nm. According to the super-hydrophobic matte composite coating and the preparation method thereof, the bottom layer and the hydrophobic structure layer are formed on the ABS base material through electroplating, the silicon dioxide layer is formed on the surface of the hydrophobic structure layer through vacuum ion plating, and the super-hydrophobic micro-nano structure layer which is low in refractive index, high in light transmittance and in a diffuse scattering matte state is formed on the surface of the ABS base material; the composite coating has low surface energy and super-hydrophobic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a composite coating for material surface treatment and a preparation method thereof. Background Art

[0002] When droplets exist stably on a solid surface, they will present different morphologies, which are represented by the contact angle (CA). The contact angle refers to the tangent of the gas-liquid interface at the intersection of gas, liquid and solid. The angle θ between this tangent on the liquid side and the solid-liquid boundary line has a value range of (0, 180). The critical contact angle value of hydrophobicity is 90°. A value greater than 90° is defined as hydrophobic. The larger the contact angle, the better the hydrophobicity of the surface. The wetting state with a contact angle greater than 150° is defined as superhydrophobic. That is, static droplets tend to maintain a spherical shape on the surface. The study also found that a static contact angle greater than 150° is not enough to characterize hydrophobicity. Therefore, the sliding angle (SA) was introduced to characterize the dynamic wettability. The sliding angle refers to the angle from the inclined surface to the point where the droplet begins to roll. At present, the literature generally defines surfaces with CA>150° and SA<10° as superhydrophobic surfaces.

[0003] Superhydrophobic surfaces with a static contact angle (CA) greater than 150° and a sliding angle (SA) less than 10° play an important role in interface applications due to their excellent waterproofing, self-cleaning, anti-corrosion protection, anti-icing and microfluidic properties.

[0004] Inspired by the super-hydrophobic phenomenon in nature (such as lotus leaves, geckos, rose petals, etc.), many years of research have reached a general consensus that the way to achieve super-hydrophobic properties is to construct a super-hydrophobic surface. According to the classic Wenzel and Cassie model, the two basic factors of appropriate roughness and low surface energy are essential for designing artificial super-hydrophobic surfaces: roughening low-surface-energy materials and reducing the surface energy of rough surfaces. One is to change the roughness through the surface micro-nano composite structure to obtain hydrophobicity; the other is to combine with low-surface-energy materials to reduce the surface energy.

[0005] Kitchen and bathroom products (such as shower heads) are in close contact with tap water, dirt, detergents, etc. during use. Stains are easily left on the surface and are difficult to clean, which affects the appearance and is not conducive to corrosion resistance. There is a real need for super-hydrophobic surfaces. However, the inevitable contact will cause wear of the surface micro-nano structure, and even slight damage to the surface roughness will lead to a significant decrease in hydrophobic performance and failure. At present, the super-hydrophobic surface of kitchen and bathroom products is mainly achieved by powder spraying. The particles used in the spraying technology are mostly colored particles, which is not suitable for metal surfaces and color surfaces with high transparency requirements. A super-hydrophobic micro-nano structure with low refractive index and high light transmittance, diffuse scattering matte state, and low surface energy is obtained for the surface of kitchen and bathroom products, so that the product has super-hydrophobic properties. Summary of the invention

[0006] The purpose of the present invention is to provide a super-hydrophobic matte composite coating and a preparation method thereof.

[0007] The technical solution of the present invention is achieved by the following methods:

[0008] The invention discloses a super-hydrophobic matte composite coating, comprising an ABS substrate; a semi-bright nickel layer, a pearl nickel layer and a trivalent chromium layer are electroplated in sequence on the upper surface of a bottom layer of the ABS substrate to form a hydrophobic structure layer; under vacuum conditions, a silicon dioxide layer with a thickness of 10-20 nm is formed on the surface of the hydrophobic structure layer of the ABS substrate by ion plating.

[0009] As a further limitation of the present invention, the raw material components of the semi-bright nickel layer include the following components: nickel sulfate NiSO4-6H2O with a concentration of 260-340 g / L, nickel chloride NiCl-5H2O with a concentration of 35-55 g / L and boric acid H3BO3 with a concentration of 30-65 g / L.

[0010] As a further limitation of the present invention, the pearl nickel layer is electroplated using an electroplating solution having the following components: nickel sulfate NiSO4-6H2O concentration of 450-530 g / L, nickel chloride NiCl-5H2O concentration of 25-55 g / L, boric acid H3BO3 concentration of 30-50 g / L, saccharin sodium C7H4NNaO3S concentration of 90-110 g / L, and octylphenol polyvinyl ether concentration of 15-40 g / L.

[0011] As a further limitation of the present invention, the raw material components of the trivalent chromium layer include the following components: butynediol BOZ with a concentration of 0.1-0.2 g / L, boric acid H3BO3 with a concentration of 43-83 g / L and trivalent chromium ions with a concentration of 11-31 g / L.

[0012] As a further limitation of the present invention, the silicon dioxide layer is coated by medium frequency magnetron sputtering with a silicon target having a purity of 99.99%, a medium frequency power supply having a frequency of 40KHZ, Ar as a sputtering gas, and O2 as a reaction gas.

[0013] The present invention also discloses a method for preparing a super-hydrophobic matte composite coating, which is applied to the above-mentioned super-hydrophobic matte composite coating, and the preparation steps include:

[0014] S1. Electroplating a semi-bright nickel layer, electroplating a semi-bright nickel layer on a clean ABS substrate;

[0015] S2. electroplating a pearl nickel layer, electroplating a pearl nickel layer on the obtained semi-nickel light layer;

[0016] S3. electroplating a trivalent chromium layer, and performing a trivalent chromium layer electroplating treatment on the obtained pearl nickel layer;

[0017] S4. vacuum coating, magnetron sputtering silicon dioxide layer on the trivalent chromium layer of the cleaned and dried ABS substrate.

[0018] As a further limitation of the present invention, the electroplating solution of the trivalent chromium layer comprises: 0.1-0.2 g / L butynediol BOZ, 43-83 g / L boric acid H3BO3 and 11-31 g / L metal chromium anode electrochemical dissolution, and the process conditions are: pH value 2.4-3, temperature 30-40 ° C, current density 2.5-4.5 A / dm 2 , time is 950-1150s.

[0019] As a further limitation of the present invention, the electroplating solution components of the semi-nickel light layer include: nickel sulfate NiSO4-6H2O concentration 260-340g / L, nickel chloride NiCl-5H2O concentration 35-55g / L and boric acid H3BO3 concentration 30-65g / L; its process conditions are: working time 1100-1250s, pH range 3.7-4.3, current 1100A, current density 2.5-4.5A / dm 2 .

[0020] As a further limitation of the present invention, the electroplating solution components of the pearl nickel layer include: nickel sulfate NiSO4-6H2O concentration 450-530g / L, nickel chloride NiCl-5H2O concentration 25-55g / L, boric acid H3BO3 concentration 30-50g / L, saccharin sodium C7H4NNaO3S concentration 90-110g / L, octylphenol polyvinyl ether concentration 15-40g / L, and its process conditions are: electroplating time 400-480s, pH value 3.8-4.4, temperature 50℃-60℃, current 1600A, current density 2.5-4.5A / dm 2 .

[0021] As a further limitation of the present invention, the ABS substrate treated by electroplating in S4 is cleaned and dried and then placed in a vacuum chamber. When the vacuum is 1*10 -3 Pa, argon gas was introduced and the pressure of the vacuum chamber was adjusted to 2*10 -3 Pa, pulse bias is 120V, duty cycle is 20%, vacuum is evacuated to 1.0*10Pa, sputtering pressure is 1.2Pa, argon is used to pre-sputter the target surface for more than 10min to remove surface oxides and other impurities, oxygen is introduced, sputtering power is 0.8-2KW, oxygen flow rate is 20-50sccm, argon flow rate is 150-200sccm, sputtering pressure is 0.6Pa, sputtering deposition time is 30-60mim, and it is taken out after cooling.

[0022] Beneficial effects of the super-hydrophobic matte composite coating and the preparation method thereof of the present invention:

[0023] The composite coating surface of the ABS substrate has numerous lotus leaf-like micro-nano circular pits with compact overlapping structures. The surface roughening has a diffuse reflection effect on light refraction, high astigmatism, structural contact angle CA>153°, and rolling angle SA<10°. The sputtered silicon dioxide layer is a polyhedral network structure ion crystal coating with a dielectric constant>3.9, low surface energy characteristics, and super hydrophobicity. The surface morphology of the silicon dioxide layer is smooth and dense, abrasion-resistant, and has high light transmittance, and can present a matte super hydrophobic composite coating with pearl satin color. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0025] Figure 1 It is a structural schematic diagram of a super-hydrophobic matte composite coating of the present invention;

[0026] Figure 2 The present invention is a flow chart of a method for preparing a super-hydrophobic matte composite coating.

[0027] Figure 3a-3d This is the microscopic morphology of the super-hydrophobic matte composite coating of Example 1 of the present invention under a JSM-6700F cold field emission scanning electron microscope.

[0028] Figure 4a It is a schematic diagram of the contact angle CA and the rolling angle SA of the super-hydrophobic matte composite coating of Example 1 of the present invention.

[0029] Figure 4b The contact angle CA and the rolling angle SA of the super-hydrophobic matte composite coating of Example 1 of the present invention are tested by a JC2000C1 contact angle measuring instrument, and a micro-injector is used to drop deionized water liquid. The volume of each drop of liquid is about 8 μL. The angle measurement method is used for testing, wherein the contact angle CA in the left figure is greater than 150°, and the rolling angle SA in the right figure is less than 10°.

[0030] Figure 5 This is a characteristic diagram of the durability of the surface superhydrophobic performance of the superhydrophobic matte composite coating after the tangential wear test of Example 1 of the present invention, wherein the prepared superhydrophobic sample is placed face down on 1.7μm (1500 mesh) sandpaper, and a weight of 10g is applied to the sample, and then the sample is moved at a speed of 5mm / s, and the contact angle of the sample is measured every 5s. After 60s, the sample still has a contact angle of more than 150°, indicating that the measured sample has good durability.

[0031] Figure 6 This is a characteristic diagram of the durability of the surface super-hydrophobic performance of the super-hydrophobic matte composite coating of Example 1 of the present invention after the impact test, wherein, by using sand particles with a diameter of 120 to 260 μm as impact objects, an impact test is performed on the sample surface tilted at 45° to test the mechanical durability of the super-hydrophobic composite coating prepared by the present invention. This impact can significantly change the microscopic morphology of the surface, thereby completely destroying the super-hydrophobic performance of the surface. The sand particle impact experiment shows that after the sand layer is impacted from a height of 2 m for 15 minutes, the static contact angle of water does not change, and the sliding angle increases to 30°. The test shows that its surface still maintains super-hydrophobic properties.

[0032] Figure 7 The super-hydrophobic matte composite coating of Example 1 of the present invention is subjected to an extinction rate test (silicon dioxide layer transparency test) by an infrared spectrometer, and the refractive characteristic diagrams under different sputtering power conditions are compared.

[0033] Reference numerals: ABS substrate 10; semi-bright nickel layer 20; pearl nickel layer 30; trivalent chromium layer 40; silicon dioxide layer 60 DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] like Figure 1 and Figure 2 As shown, the present invention provides a method for preparing a super-hydrophobic matte composite coating, on the basis of electroplating the surface of an ABS material to form a bottom layer, a semi-bright nickel layer 20, a pearl nickel layer 30 and a trivalent chromium layer 40 are electroplated in sequence on the upper surface of the bottom layer of an ABS substrate 10 to form a hydrophobic structure layer; and under vacuum conditions, a 10-20nm thick silicon dioxide layer 60 is formed on the surface of the hydrophobic structure layer of the ABS substrate 10 by ion plating, so as to form a super-hydrophobic matte composite coating, which has low surface energy characteristics and super-hydrophobicity, and also has the characteristics of being smooth and dense, abrasion-resistant, high light transmittance, high light dispersion, and can present a matte effect of pearl satin color.

[0037] The pretreatment of the ABS substrate 10 is to pretreat the electroplating grade ABS substrate 10 through roughening, reduction, pre-impregnation, palladium activation, debonding, pre-nickel plating, and bright copper to form a bottom layer for the subsequent electroplating process. The specific steps include:

[0038] (1) Roughening: the roughening electroplating solution is 300-400g / L chromic anhydride and 350-400g / L sulfuric acid. The process conditions are: working temperature is 35-55°C, and the roughening time is 450-900s. The roughened surface is washed with water for 10-20s.

[0039] (2) Reduction: The roughened ABS substrate 10 is placed in 30-40 ml / L stannous chloride SnCl2 for reduction for 60-100 seconds; after reduction, it is washed with water for 10-15 seconds;

[0040] (3) pre-dipping, pre-dipping the reduced ABS substrate 10 in hydrochloric acid with a concentration of 180-250 mL / L for 120-130 seconds;

[0041] (4) Palladium activation: soak the pre-impregnated ABS substrate 10 in a composite activation solution of 200-300 ml / L hydrochloric acid, 25 g / L stannous chloride and 30-50 ppm palladium chloride PdCl2 for 180-200 seconds at room temperature, and wash with water after soaking;

[0042] (5) Degumming: immersing the palladium-activated ABS substrate 10 in a 50 g / L sodium hydroxide solution for 60-120 seconds. The ABS substrate 10 does not deform. After degumming, the substrate is washed with water.

[0043] (6) Pre-nickel plating: the debonded ABS substrate 10 is pre-plated with nickel. The components of the electroplating solution are: nickel sulfate NiSO4-7H2O concentration 220-300 g / L, nickel chloride NiCl-5H2O concentration 40-60 g / L, boric acid H3BO3 concentration 30-50 g / L; pH value 3.7-4.3, temperature 50-60° C., time 420-440 s, current 1100 A, current density 1.5-3.0 A / dm2 ; and wash with water;

[0044] (7) Bright copper: The pre-nickel-plated ABS substrate 10 is electroplated with copper. The electroplating solution composition is: copper sulfate CuSO4 concentration 160-240 g / L, sodium chloride NaCl concentration 8-10 g / L, time 220-300 s, temperature 22-30° C., current 1200 A, current density 2.5-4.5 A / dm 2 .

[0045] Semi-bright nickel layer 20, before electroplating the semi-bright nickel layer 20, the pre-treated ABS substrate 10 is acid activated, that is, soaked in sulfuric acid H2SO4 with a concentration of 20-30ml / L at room temperature for 60s, and then washed with water. The acid-activated ABS substrate 10 is electroplated in a composition of nickel sulfate with a concentration of 260-340g / L, nickel chloride NiCl-5H2O with a concentration of 35-55g / L, and boric acid H3BO3 with a concentration of 30-65g / L; the process conditions are: time 1100-1250s, pH value 3.7-4.3, current 1100A, current density 2.5-4.5A / dm 2 , and wash with water.

[0046] The pearl nickel layer 30 is electroplated on the surface of the semi-bright nickel layer 20. The electroplating solution comprises: nickel sulfate NiSO4-6H2O concentration of 450-530 g / L, nickel chloride NiCl-5H2O concentration of 25-55 g / L, boric acid H3BO3 concentration of 30-50 g / L, saccharin sodium C7H4NNaO3S concentration of 90-110 g / L, octylphenol polyvinyl ether (OP-10) concentration of 15-40 g / L, and the process conditions are: electroplating time of 400-480 s, pH value of 3.8-4.4, temperature of 50°C-60°C, current of 1600 A, and current density of 2.5-4.5 A / dm 2 , and wash with water.

[0047] The trivalent chromium layer 40 is electroplated on the surface of the pearl nickel layer 30. The electroplating solution composition is: 0.1-0.2g / L butynediol BOZ, 43-83g / L boric acid H3BO3 and 11-31g / L metal chromium anode electrochemical dissolution, pH value is 2.4-3, temperature is 30-40°C, current density is 2.5-4.5A / dm 2 , the time is 950-1150s; after the electroplating is completed, hot water washing and drying are carried out at a temperature of 40℃-60℃ and a time of 140-160s; the drying temperature is 40℃-55℃ and the drying time is 1600-1800s.

[0048] Silica layer 60. The ABS substrate 10 is pretreated, electroplated with a semi-bright nickel layer 20, a pearl nickel layer 30 and a trivalent chromium layer 40 to form a hydrophobic structure layer. After washing, it is placed in a vacuum chamber, and the vacuum is pumped by a mechanical pump and a molecular pump. When the vacuum reaches 1*10 -3 Pa, close the high valve and introduce argon gas. By adjusting the argon gas flow rate, the air pressure in the vacuum chamber is adjusted to 20 Pa. Turn on the pulsed bias voltage, the power supply voltage is 120 V, and the duty cycle is 20%. Pump the vacuum to 1.0*10 Pa, the sputtering air pressure is 1.2 Pa, pre-sputter the surface of the target material with argon gas for more than 10 minutes to remove oxides and other impurities on the surface of the target material. Introduce oxygen gas into the vacuum chamber. After the glow is stable, open the baffle. Keep the sputtering power at 0.8 KW, the oxygen gas flow rate at 20 sccm, the argon gas flow rate at 150 sccm, the sputtering air pressure at 0.6 Pa, and the sputtering deposition time at 30 minutes to complete the vacuum ion plating. Continue to operate the cooling system for 1 hour, open the vacuum chamber and take out. The thickness of the silica layer 60 is 10 nm.

[0049] It should be noted that for the pretreated ABS substrate 10, a semi-bright nickel layer, a pearl nickel layer and a trivalent chromium layer are sequentially electroplated on the surface. Under vacuum conditions, a silica layer is formed by ion plating. Therefore, a super-hydrophobic matte composite coating is formed on the surface of the ABS substrate. The surface of the composite coating has an infinite number of micro-nano circular concave cavities similar to lotus leaves in a tightly overlapping structure. The surface roughening of the composite coating results in a diffuse reflection state for the light refraction effect. The contact angle CA of the structure is >153°, and the rolling angle SA <10°. The sputtered silica layer is a polyhedral network structure ionic crystal coating with a dielectric constant >3.9, having low surface energy characteristics and super-hydrophobicity. It can be seen from the measurement and analysis of the surface morphology obtained by atomic force microscopy AFM that the surface morphology of the silica thin film is smooth and dense, (density >2.2 g / cm-3), wear-resistant. The silica coating particles have a high light transmittance (refractive index 1.1 - 1.46) and a high light scattering rate (glossiness 20 <GU), presenting a matte super-hydrophobic composite coating of ABS products with the color of pearl satin.

[0050] Example 2

[0051] The preparation method is basically the same as that of Example 1. The difference is that for the vacuum coating of the silica layer 60, the sputtering power in the vacuum chamber is maintained in the range of 1.5 KW, the oxygen gas flow rate is 35 sccm, the argon gas flow rate is 180 sccm, the sputtering air pressure is 0.6 Pa, and the sputtering deposition time is 45 minutes to complete the vacuum ion plating. Continue to operate the cooling system for 1 hour, open the vacuum chamber and take out. The thickness of the silica layer 60 is 14 nm.

[0052] Example 3

[0053] The preparation method is basically the same as that of Example 1, except that, for the vacuum coating of the silicon dioxide layer 60, the vacuum chamber maintains the sputtering power in the range of 2 kW, the oxygen flow rate is 50 sccm, the argon flow rate is 200 sccm, the sputtering pressure is 0.6 Pa, the sputtering deposition time is 60 min, the vacuum ion plating is completed, the cooling system is continued to operate for 1 hour, the vacuum chamber is opened and taken out, and the thickness of the silicon dioxide layer 60 is 20 nm.

[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A super-hydrophobic matte composite coating, characterized in that: include: ABS substrate; The upper surface of the bottom layer of the ABS substrate is electroplated with a semi-bright nickel layer, a pearl nickel layer and a trivalent chromium layer in sequence to form a hydrophobic structure layer; Under vacuum conditions, a silicon dioxide layer with a thickness of 10-20 nm is formed by ion plating on the surface of the hydrophobic structure layer of the ABS substrate.

2. The super-hydrophobic matte composite coating according to claim 1, characterized in that: The raw material components of the semi-bright nickel layer include the following components: nickel sulfate NiSO4-6H2O with a concentration of 260-340 g / L, nickel chloride NiCl-5H2O with a concentration of 35-55 g / L and boric acid H3BO3 with a concentration of 30-65 g / L.

3. The super-hydrophobic matte composite coating according to claim 2, characterized in that: The pearl nickel layer is electroplated with an electroplating solution having the following components: nickel sulfate NiSO4-6H2O concentration of 450-530 g / L, nickel chloride NiCl-5H2O concentration of 25-55 g / L, boric acid H3BO3 concentration of 30-50 g / L, saccharin sodium C7H4NNaO3S concentration of 90-110 g / L, and octylphenol polyvinyl ether concentration of 15-40 g / L.

4. The super-hydrophobic matte composite coating according to claim 3, characterized in that: The raw material components of the trivalent chromium layer include the following components: butynediol BOZ with a concentration of 0.1-0.2 g / L, boric acid H3BO3 with a concentration of 43-83 g / L, and trivalent chromium ions with a concentration of 11-31 g / L.

5. The super-hydrophobic matte composite coating according to claim 4, characterized in that: The silicon dioxide layer is coated with a silicon target having a purity of 99.99% by medium frequency magnetron sputtering, a medium frequency power supply having a frequency of 40 kHz, Ar as a sputtering gas, and O2 as a reaction gas.

6. A method for preparing a super-hydrophobic matte composite coating, applied to the super-hydrophobic matte composite coating as claimed in any one of claims 1 to 5, characterized in that: The preparation steps include: S1. Electroplating a semi-bright nickel layer, electroplating a semi-bright nickel layer on a clean ABS substrate; S2. electroplating a pearl nickel layer, electroplating a pearl nickel layer on the obtained semi-bright nickel layer; S3. electroplating a trivalent chromium layer, and performing a trivalent chromium layer electroplating treatment on the obtained pearl nickel layer; S4. vacuum coating, magnetron sputtering silicon dioxide layer on the trivalent chromium layer of the cleaned and dried ABS substrate.

7. The preparation method according to claim 6, characterized in that: The electroplating solution of the trivalent chromium layer includes: 0.1-0.2g / L butynediol BOZ, 43-83g / L boric acid H3BO3 and 11-31g / L metal chromium anode electrochemical dissolution, and the process conditions are: pH value 2.4-3, temperature 30-40°C, current density 2.5-4.5A / dm 2 , time is 950-1150s.

8. The preparation method according to claim 7, characterized in that: The electroplating solution components of the semi-bright nickel layer include: nickel sulfate NiSO4-6H2O concentration 260-340g / L, nickel chloride NiCl-5H2O concentration 35-55g / L and boric acid H3BO3 concentration 30-65g / L; its process conditions are: working time 1100-1250s, pH range 3.7-4.3, current 1100A, current density 2.5-4.5A / dm 2 .

9. The preparation method according to claim 8, characterized in that: The electroplating solution components of the pearl nickel layer include: nickel sulfate NiSO4-6H2O concentration 450-530g / L, nickel chloride NiCl-5H2O concentration 25-55g / L, boric acid H3BO3 concentration 30-50g / L, saccharin sodium C7H4NNaO3S concentration 90-110g / L, octylphenol polyvinyl ether concentration 15-40g / L, and the process conditions are: electroplating time 400-480s, pH value 3.8-4.4, temperature 50℃-60℃, current 1600A, current density 2.5-4.5A / dm 2 .

10. The preparation method according to claim 9, characterized in that: After the ABS substrate treated by electroplating in step S4 is cleaned and dried, it is placed in a vacuum chamber. When the vacuum is 1*10 -3 Pa, introduce argon, adjust the pressure of the vacuum chamber to 20Pa, the pulse bias voltage to 120V, the duty cycle to 20%, evacuate to 1.0*10Pa, the sputtering pressure to 1.2Pa, pre-sputter the target surface with argon for more than 10min to remove surface oxides and other impurities, introduce oxygen, the sputtering power is 0.8-2KW, the oxygen flow rate is 20-50sccm, the argon flow rate is 150-200sccm, the sputtering pressure is 0.6Pa, the sputtering deposition time is 30-60mim, and take it out after cooling.